Virtual lab in Modelica of a cement clinker cooler for operator training (2014)
Plant operator training plays a fundamental role in improving the energy efficiency of the cement manufacturing process and in reducing the CO2 emission. A virtual lab of a clinker grate cooler, intended for the training of cement plant operators, has been developed. The grate cooler model has been derived from first principles, and has been validated by consulting cement industry experts, and comparing the simulated results with published data and available information from the cement industry. The model has been described in the Modelica language. The Interactive Modelica library has been used to develop the interactive user-to-model interface, and the communication between this interface and the model. The virtual lab, which is completely described in Modelica, has been simulated using the Dymola 6.1 modelling environment. The Interactive Modelica library can be freely downloaded from the website http://www.euclides.dia.uned.es/. © 2013 © Taylor & Francis.